2003
DOI: 10.1590/s0103-50532003000500007
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved fluorescence anisotropy of basic dyes bound to poly(methacrylic acid) in solution

Abstract: Soluções de poli(ácido metacrílico) atático, PAMA com peso molecular na faixa de (1,6 a 3,4) x 10 5 g mol -1 , e com corantes fluorescentes 9-aminoacridina ou azul do nilo ligados à cadeia, foram estudados por medidas fotofísicas em função da viscosidade e polaridade do solvente. O comportamento dos segmentos da cadeia do PAMA nas vizinhanças da sonda fluorescente foi descrito pela mudança na rotação difusional dos corantes. O etilenoglicol expande a cadeia polimérica quando comparada com a forma mais compacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…Intramolecular rotations of the dye molecules can be counterproductive to the quantum efficiency since they can invoke a deactivation of the S 1 excited state and consequently lower the quantum yield. 17 In the context of PBE lasing, a recent report 9 related the viscosity of the liquidcrystal phase to the photoluminescence intensity of the dye. Upon cooling from the liquid crystalline to the glass phase a large increase in the photoluminescence was observed, corresponding to a large increase in the viscosity.…”
Section: Temperature-dependent Lasingmentioning
confidence: 99%
“…Intramolecular rotations of the dye molecules can be counterproductive to the quantum efficiency since they can invoke a deactivation of the S 1 excited state and consequently lower the quantum yield. 17 In the context of PBE lasing, a recent report 9 related the viscosity of the liquidcrystal phase to the photoluminescence intensity of the dye. Upon cooling from the liquid crystalline to the glass phase a large increase in the photoluminescence was observed, corresponding to a large increase in the viscosity.…”
Section: Temperature-dependent Lasingmentioning
confidence: 99%
“…5(a). The crowding dye chains form a compact or contracted coil in which the dye is embedded [35]. This effect increases the local viscosity [35], which in our view is the reason behind the larger decay time of Cytate in cancerous prostate tissue compared to that in normal prostate tissue samples.…”
Section: B Time-resolved Fluorescence Polarization Anisotropy Of Cytmentioning
confidence: 69%
“…The products were precipitated in acetone, centrifuged, and washed several times with acetone to remove the non-reacting dye and monomer. The tacticity of the dye-PMAA samples was determined by 13 C and 1 H NMR measurements in D 2 O solutions, and indicated that all samples are atactic [32].…”
Section: Methodsmentioning
confidence: 99%
“…The amount of dye was determined from the UVVisible absorption of a polymer solution assuming for the molar extinction coefficient the value of the free dye in the same solvent [30][31][32]. In general, the incorporation of the dyes into the polymer chain was low with average number less than 1.…”
Section: Polymer Propertiesmentioning
confidence: 99%